Relationship Between Mothers' Knowledge and the Incidence of Stunting in Children Aged 2-5 Years - Karolina Sulistio Tete; Baharika Suci Dwi Aningsih; Eviyani Margaretha Manungkalit; Dyah Woro Kartiko Kusumo Wardani; Frenta Helena Simaibang (Jurnal EduHealth, 2025)
Stunting is a chronic disorder caused by malnutrition that inhibits growth and development in toddlers. One factor influencing the success of exclusive breastfeeding is knowledge about how to optimize a child's growth and development, particularly during the toddler years, which requires preparation on the part of both mothers and health workers. This study aims to determine the relationship between mothers' knowledge and the incidence of stunting in children aged 2-5 years at the District Health Center. This study uses a descriptive analytical design with a cross-sectional approach. Data collection tools use a questionnaire on mothers' knowledge about stunting. The sample in this study consisted of 52 respondents. The sample was determined using the Slovin formula. The statistical test used was the chi-square test, which showed that 52 mothers had a basic education level, namely 9 (17.3%); 24 (46.2%) had a secondary education level; and 19 (36.5%) had a higher education level. The frequency distribution of knowledge among the 52 mothers showed that most had satisfactory knowledge about stunting, totaling 36 (69.2%), sufficient knowledge in 16 (30.8%), and insufficient knowledge in 0%. This shows that of the 52 toddlers with stunting, most were in the short category (21 or 40.4%) and normal category (31 or 59.6%). The data collection results show that out of 52 respondents, most children were in the normal category (31 or 59.6%), short category (21 or 40.4%), and very short category (0%). The results of the data analysis test on the relationship between mothers' knowledge and stunting in toddlers aged 2-5 years old at the district health center showed that mothers with good knowledge had 11 (14.1%) short toddlers and 25 (20.9%) normal toddlers, while mothers with adequate knowledge had 10 (6.9%) short toddlers and 6 (10.1%) normal toddlers. This study obtained a significant value of (P-value=0.030), with a sig value of (0.030)< 0.05, meaning that there is a significant correlation or relationship between the level of maternal knowledge and the incidence of stunting in toddlers aged 2-5 years at the District Health Center.